Above‐ground carbon assessment in the Kom‐Mengamé forest conservation complex, South Cameroon: Exploring the potential of managing forests for biodiversity and carbon. (30th July 2014) - Fongnzossie, Evariste Fedoung; Sonwa, Denis Jean; Kemeuze, Victor; Auzel, Phillipe; Nkongmeneck, Bernard‐Aloys
Abstract Protected areas are important for biodiversity conservation and the maintenance of ecosystem services, including climate regulation through carbon storage. Yet, there is little knowledge of their carbon storage potential. This study assesses the above‐ground carbon stock and the congruence between carbon stock and tree diversity in the Kom‐Mengamé forest conservation complex (KMFCC) in South‐Cameroon, based on an inventory of trees with DBH ≥ 10 cm in 1, 366 plots (100 × 5 m each) covering 63.8 ha, established in different land use types (terra firma forest, swamp forest and cultivated areas). Above‐ground carbon was estimated using generic allometric equation and species‐specific wood density derived from wood density databases. Results showed high carbon stock in KMFCC with values ranging from 143.29 ± 124.37 Mg/ha‐1 in swamp areas to 240 ± 204.35 Mg/ha‐1 in terra firma forests. Mean carbon stock in managed areas differed from that of terra firma forests. Petersianthus macrocarpus showed the greatest carbon stock. The study demonstrates the need for integrated approaches for carbon management in secondary forests where agroforests might be important to maintain biodiversity associated with high carbon storage. These approaches are particularly relevant to the Congo basin region where protected areas are threatened by poor management of their periphery.